A two-step approach combining FK with SE for simulating ground motion due to point dislocation sources. Issue 157 (June 2022) - Ba, Zhenning; Wu, Mengtao; Liang, Jianwen; Zhao, Jingxuan; Lee, Vincent W.
Abstract: It has been well established that source-path-site effects have had an essential impact on the seismic analysis of major infrastructure over the past few decades, where the accurate and efficient modeling of seismic wave propagation can become a critical issue. In this study, a two-step approach combining the frequency-wavenumber (FK) technique with the spectral element (SE) method is developed based on the concept of domain reduction to simulate three-dimensional (3D) ground motion due to point dislocation sources. In the first step, the seismic responses for the dislocations in a layered half-space crustal model are solved exactly using the FK method and converted into effective input seismic loads around the region of interest. In the second step, the local wavefields of a 3D complex site are finely simulated using the SEM, while absorbing conditions are imposed at five boundaries of the SE model to achieve absorption of the outward scattered energy. The semi-analytical FK method is well-matched to the propagation frequencies because it allows the broadband synthesis associated with engineered systems to be addressed without additional calculations. When the FK is combined with the SEM, it is feasible to efficiently simulate earthquake ground motions covering a broad range of frequencies in the region of interest. Comparisons with the results of existing studies and the traditional SEM show that our approach is accurate and robust for arbitrary geometries and point sources. To further illustrate the efficiency and general applicability of the proposed method, three examples are presented. The results demonstrate that the two-step approach can consider the effects of the seismic source, propagation path, and local site geological conditions on the earthquake ground motions and serve as an effective forward modeling tool for reducing the computational cost. Highlights: The FK and SEM are hybridized to simulate seismic response of a 3D complex layered site. The presented methodology is programmed and well verified by comparison with existing solutions. The effects of the source-, propagation-, and site conditions on ground motions are studied. The proposed two-step approach reduces computational cost in source-path-site modeling.